1972
DOI: 10.1073/pnas.69.4.912
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Course of Evolution of Wheat

Abstract: Chromosome pairing in hybrids involving Triticum aestivum and new accessions of T. speltoides, and in an amphiploid of these species, indicates that T. speltoides can no longer be considered to be the donor of the B genome of the polyploid wheats. This necessitates a reconsideration of the genome relationships and evolutionary processes that gave rise to cultivated wheats.The evolutionary processes and the species involved in the origin of wheat (Triticum aestivum, L.; 2n = 6x = 42) have been the subject of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0
6

Year Published

1976
1976
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 7 publications
3
48
0
6
Order By: Relevance
“…On the other hand, Kimber and Athwal (1972) considered polyphyletic origin of B genome, i.e. the present B genome being a recombinant genome between two putative B genomes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Kimber and Athwal (1972) considered polyphyletic origin of B genome, i.e. the present B genome being a recombinant genome between two putative B genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Ae. speltoides is naturally variable for the ability to elicit homeologous chromosome pairing in hybrids with wheat (Dvorak 1972;Kimber and Athwal 1972). A virtual continuum of chromosomepairing levels, ranging from a few to $16 chiasmata/ metaphase I (MI) cell, has been observed in various T. aestivum 3 Ae.…”
mentioning
confidence: 99%
“…(10). However, the chromosomes of T. speltoides pair poorly with the chromosomes of the B genome (11)(12)(13), and it was concluded that T. speltoides could not be a source of the B genome (12). Since the chromosomes of the G genome of T. timopheevii pair, albeit poorly, with the chromosomes of the B genome, the B and G genomes must be very closely related (14,15).…”
mentioning
confidence: 99%